2021
DOI: 10.1002/jgc4.1472
|View full text |Cite
|
Sign up to set email alerts
|

Spanish language concordance in genetic counseling sessions in the United States: Counselor experiences and perceptions of its effects on processes and outcomes

Abstract: Prior research suggests language concordance positively affects physician-patient communication and their relationship, but few studies have investigated language concordance in genetic counseling sessions for Spanish-speaking patients. This study explored Spanish-speaking genetic counselors' experiences and perceptions of the effects of Spanish language concordance on session processes and outcomes using the Reciprocal-Engagement Model (REM) of practice as a conceptual framework.There are 17 REM goals associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
4
6
0
Order By: Relevance
“…Our results align with literature on the role of communication in clinical research, and the extent to which the quality and consistency of communication may influence patient identification and enrollment practices ( Sae-Hau et al, 2021 ) Language-concordant engagement has been shown to facilitate navigation of clinical genetic services for individuals with limited English proficiency ( Pacyna et al, 2021 ; de Leon et al, 2022 ) Our study suggests that resources for communication may be equally important in genomics research, where concepts and terminology are very complex and non-native English speakers who do not typically need an interpreter may struggle with communication. Given that nearly one in 10 adults in the United States have limited English proficiency, language-concordant research services are an essential tool for inclusive research ( Ryan, 2013 )…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results align with literature on the role of communication in clinical research, and the extent to which the quality and consistency of communication may influence patient identification and enrollment practices ( Sae-Hau et al, 2021 ) Language-concordant engagement has been shown to facilitate navigation of clinical genetic services for individuals with limited English proficiency ( Pacyna et al, 2021 ; de Leon et al, 2022 ) Our study suggests that resources for communication may be equally important in genomics research, where concepts and terminology are very complex and non-native English speakers who do not typically need an interpreter may struggle with communication. Given that nearly one in 10 adults in the United States have limited English proficiency, language-concordant research services are an essential tool for inclusive research ( Ryan, 2013 )…”
Section: Discussionsupporting
confidence: 86%
“…Our results align with literature on the role of communication in clinical research, and the extent to which the quality and consistency of communication may influence patient identification and enrollment practices (Sae-Hau et al, 2021) Language-concordant engagement has been shown to facilitate navigation of clinical genetic services for individuals with limited English proficiency (Pacyna et al, 2021;de Leon et al, 2022) Our study suggests that resources for communication may be equally important in genomics research, where concepts and terminology are very complex and non-native English speakers who do not typically need an interpreter may struggle with communication. Given that nearly one in 10 adults in the United States have limited English proficiency, language-concordant research services are an essential tool for inclusive research (Ryan, 2013) Our findings also intersect in unexpected ways with the literature on the role of trust in recruitment of historically marginalized communities in clinical genomics research (George et al, 2013;Claw et al, 2018;Kraft et al, 2018;Lee et al, 2019;Armstrong and Ritchie, 2022) While this literature has emphasized trust-and specifically mistrust-as a barrier to clinical genomics research participation, Hispanic parents in our study expressed more trust in providers to identify and refer them to clinical genomics research than other parents.…”
Section: Discussionsupporting
confidence: 85%
“…The Reciprocal Engagement Model of genetic counseling highlights the significance of relationship between GC and patient by having this relationship at the core of the counseling process: “The relationship serves as the conduit, providing an alliance in which the patient feels supported, cared about, connected, and validated.” (McCarthy Veach et al, 2007). The results of the present study suggest that language concordance between the GC and patient allowed patients to feel emotionally supported, empowered, and comfortable in sessions, a finding that has been supported in recent genetic counseling studies (Carmichael et al, 2021; de Leon et al, 2022; Garza et al, 2020). Furthermore, while not directly studied here, cultural concordance could have also played a role, which is suggested by previous research as highlighted by this quote: “Women from ethnic minorities may find it difficult to develop a trusting relationship with health‐service providers of different cultural backgrounds, especially ones with whom they have had no prior relationship” (Browner et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…All study participants received healthcare via medical interpreters in the past and most stated they preferred Spanish‐speaking providers due to the absence of a language barrier, a finding consistent with previous literature which supports that provider language concordance is preferred among Spanish‐speaking patients (Carmichael et al, 2021; de Leon et al, 2022; Gonzalez et al, 2010). Two participants in our study did highlight the significance of having no language barriers in the session, with one of these participants also emphasizing that cultural concordance plays a role in successful communication.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation